PEMBUATAN TINTA PRINTER DENGAN PIGMEN ORGANIK BERBAHAN DASAR SAMPAH DAUN - Wiguna, Pradita Ajeng; Susanto, Susanto (Sainteknol : Jurnal Sains dan Teknologi, 2015)
Waste became one of the unresolved issues in the society. One of the abundant number of waste is organic waste in the form of leaves. The high production of leaf litter on the environment are demanding alternative ways of handling the creative and innovative products useful. An attempt was made is the use of leaf litter as organic color pigments for ink printers. Manufacture of pigments made by reducing the leaf litter to form a homogeneous carbon powder that is burning leaf litter under conditions of low oxygen and then do a simple mixing process with other materials ink makers. The resulting ink tested of transmittance by varying the mass of carbon namely from 1 to 6 grams, the results indicate that the more carbon, the intensity of their light mass is getting low. At the time of adsorbtion rate test showed that carbon ink has almost the same velocity with the type of ink that is circulating in the market, i.e. 1.04 mm/s. Additionally carbon inks have dried faster speed compared to the existing inks on the market, i.e. the ratio of 106: 129 seconds. In the test performance of carbon ink on the printer shows the results that more black and smooth so that appropriate if applied as an inkjet printer.